2021
DOI: 10.3389/fonc.2020.607742
|View full text |Cite
|
Sign up to set email alerts
|

Re-Clustering and Profiling of Digestive System Tumors According to Microenvironment Components

Abstract: BackgroundImmunotherapy has become the most promising therapy in digestive system tumors besides conventional chemotherapy and radiotherapy. But only a few patients can benefit from different types of immunotherapies, such as immune checkpoint blockade (ICB). To identify these ICB-susceptible patients, methods are urgently needed to screen and profile subgroups of patients with different responsiveness to ICB.MethodsThis study carried out analysis on patients with digestive system tumors that were obtained fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…While PD-1 and PD-L1 are highly expressed in the high-risk group, our epigenetic results indicate that most m 6 A regulators are highly expressed in the high-risk group, and combining these two results, we conclude that the expression of PD-1 and PD-L1 is positively correlated with PCFG scores. To provide ideas for clinical personalized immunotherapy, we further analyzed the correlation of immune cell in ltration in the TIME with risk scores and suggested that patients with high scores might have plentiful immune cells incuding broblasts, endothelial cells and monocytes in ltration, which were similar to previous studies [41]. Consequently, the high-risk group may be insensitive to immunotherapy.…”
Section: Discussionsupporting
confidence: 58%
“…While PD-1 and PD-L1 are highly expressed in the high-risk group, our epigenetic results indicate that most m 6 A regulators are highly expressed in the high-risk group, and combining these two results, we conclude that the expression of PD-1 and PD-L1 is positively correlated with PCFG scores. To provide ideas for clinical personalized immunotherapy, we further analyzed the correlation of immune cell in ltration in the TIME with risk scores and suggested that patients with high scores might have plentiful immune cells incuding broblasts, endothelial cells and monocytes in ltration, which were similar to previous studies [41]. Consequently, the high-risk group may be insensitive to immunotherapy.…”
Section: Discussionsupporting
confidence: 58%
“…The CIBERSORT algorithm was used to complete the analysis of immune-infiltrating cells in each sample [18,19].…”
Section: Tumor Immune Cell Infiltration Analysismentioning
confidence: 99%